2019
DOI: 10.1088/1361-6641/ab0626
|View full text |Cite
|
Sign up to set email alerts
|

Photoconductivity, carrier lifetime and mobility evaluation of GaAs films on Si (100) using optical pump terahertz probe measurements

Abstract: The carrier lifetimes and electron mobility values were estimated for 2 μm thick GaAs films grown on Si (100) substrates by means of optical pump terahertz probe (OPTP) technique. The GaAs/Si films measured were epitaxial grown at different substrate temperatures (T S =520 °C or T S =630 °C). From x-ray diffraction measurements and Raman spectroscopy, the GaAs/Si films were shown to experience minimum strain at room temperature, and crystal misorientation in the (111) or (110) direction. With no measureabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 46 publications
3
11
0
Order By: Relevance
“…It should be noted that for LTG-GaAs on SI-GaAs, high photoexcited carrier mobility, due to high crystallinity, and the presence of few As clusters in the LTG-GaAs are two important factors for intense THz generation [16]. In a previous study, 630Si has been shown to have higher carrier mobility than 520Si attributed to the higher crystallinity of 630Si [34], which is consistent with the SEM images and Xray diffraction results presented in this work.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…It should be noted that for LTG-GaAs on SI-GaAs, high photoexcited carrier mobility, due to high crystallinity, and the presence of few As clusters in the LTG-GaAs are two important factors for intense THz generation [16]. In a previous study, 630Si has been shown to have higher carrier mobility than 520Si attributed to the higher crystallinity of 630Si [34], which is consistent with the SEM images and Xray diffraction results presented in this work.…”
Section: Resultssupporting
confidence: 90%
“…This improvement is in agreement with the increasing APD size (reduction in APB density) observed from the top-view SEM images of the GaAs on Si samples as T s is increased. The crystallinity of the grown GaAs on Si samples as observed in the SEM images and X-ray rocking curves is consistent with the measured carrier mobility presented in a previous work [34]. Raman shift on a (100) surface acquired from backscattering geometry theoretically forbids TO mode [35,36].…”
Section: Resultssupporting
confidence: 90%
“…This improvement is in agreement with the increasing APD size (reduction in APB density) observed from the top-view SEM images of the GaAs on Si samples as T s is increased. The crystallinity of the grown GaAs on Si samples as observed in the SEM images and X-ray rocking curves is consistent with the measured carrier mobility presented in a previous work [34]. Raman shift on a (100) surface acquired from backscattering geometry theoretically forbids TO mode [35,36].…”
Section: Resultssupporting
confidence: 90%
“…The presence of APBs (Figure 2) in the layer must be considered and the fast process could be better attributed to the scattering of conduction electrons on these structural defects. Minority carrier lifetime decreases when dislocation density increases in GaAs on silicon grown at higher temperatures [35], [36], and the mechanism is likely to be similar. In THz applications, the lack of trap-saturation behavior may also be favorable, as it implies consistent bandwidths (and possibly dynamic range) when operating LT-GaAs/Si devices regardless of incident laser power.…”
Section: Heteroepitaxial Growth Of Lt-gaas/simentioning
confidence: 99%